Dynamics of border tourism in the Barents Euro-Arctic Region - Elena Yu. Tereshchenko (Arctic and North, 2018)
The article discusses the main types and characteristics of border tourism in the countries of the Barents region. It provides official statistics on the number of trips, the results of tourist motivation study and reveals the positive dynamics of border tourism development. The materials of the current study include a review and comparative analysis with data obtained during research sessions since 2013 within the framework of the international program Bachelor of Northern Studies. According to the survey, the Barents region has a great potential for the development of tourism and positive motivation that contributes to international contacts. An analysis of the border tourism development dynamics has shown an increase in the demand in the tourism services market, the necessity to create programs focused on the needs of the target audience of buyers, and the active promotion of Russian tourism in the international market.